Genetic predisposition to infection in a case of atypical hemolytic uremic syndrome. Issue 1 (January 2018) - Heuvel, Lambertus; Riesbeck, Kristian; El Tahir, Omaima; Gracchi, Valentina; Kremlitzka, Mariann; Morré, Servaas; Furth, A.; Singh, Birendra; Okrój, Marcin; Kar, Nicole; Blom, Anna; Volokhina, Elena
Abstract Most cases of hemolytic uremic syndrome (HUS) are caused by infection with enterohemorrhagicEscherichia coli (EHEC). Genetic defects causing uncontrolled complement activation are associated with the more severe atypical HUS (aHUS). Non-EHEC infections can trigger the disease, however, complement defects predisposing to such infections have not yet been studied. We describe a 2-month-old patient infected with different Gram-negative bacterial species resulting in aHUS. Serum analysis revealed slow complement activation kinetics. Rare variant R229C was found in complement inhibitor vitronectin. Recombinant mutated vitronectin showed enhanced complement inhibition in vitro and may have been a predisposing factor for infection. Our work indicates that genetic changes in aHUS can not only result in uncontrolled complement activation but also increase vulnerability to infections contributing to aHUS.